Community Empowerment through Digital Entrepreneurship: The Digital Terrace Program in Tangerang - Aries Denta Putra (Inovasi Sosial : Jurnal Pengabdian Kepada Masyarakat, 2026)
The rapid advancement of digital technology has created new opportunities for communities to develop innovative and competitive entrepreneurial activities. However, the utilization of digital technology for business development remains constrained by limited digital literacy and entrepreneurial competencies. The Digital Terrace Program was implemented as a community engagement initiative aimed at enhancing community knowledge and capacity in digital entrepreneurship in Tangerang, Indonesia. The program employed a participatory approach consisting of preparation, implementation, and evaluation stages. Educational activities were conducted through interactive lectures, practical demonstrations, group discussions, and question-and-answer sessions that encouraged active participant involvement. Program evaluation was carried out through direct observation and participant reflections throughout the implementation process. The results indicate that participants developed a better understanding of digital entrepreneurship concepts, digital marketing strategies, and the effective use of digital platforms to support business activities. In addition, the program increased participants' confidence in identifying entrepreneurial opportunities and strengthened collaboration among community members. These findings suggest that participatory digital entrepreneurship education is an effective strategy for enhancing community empowerment and supporting sustainable local economic development.